A Randomized Double-Blinded Clinical Study of Early Volumetric Changes After Shunt Surgery and MRI-Resistance of the Codman Certas® Plus Shunt Valve - Holmgren, Rafael T; Nilsson, Martin; Georgiopoulos, Charalampos ; 0000-0001-8850-3742; Zsigmond, Peter (World Neurosurgery, 2025)
OBJECTIVE: Linear radiological measures have low sensitivity to detect changes in ventricular volume in patients with idiopathic normal pressure hydrocephalus. Ventricular volumetry is accurate and sensitive in detecting subtle changes in cerebrospinal fluid volumes. The Codman Certas® Plus is an adjustable shunt valve with 8 settings and resistant to magnetic resonance imaging (MRI)-induced inadvertent adjustments in vitro. The aim of this study was to investigate early volumetric changes in ventricles after ventriculoperitoneal shunting in relation to shunt setting and linear measures. We also wanted to evaluate the MRI-resistance of the Codman Certas® Plus valve in a clinical setting. METHODS: Forty-five idiopathic normal pressure hydrocephalus patients underwent quantitative MRI, including volumetry before and 36 hours after shunting with Codman Certas® Plus valves set to 4 (20 patients) and 8 (25 patients). Valve setting was blinded to patients and examiners and assessed after each MRI. Patients performed in total 156 MRI examinations during 3 years. RESULTS: There was significant difference in change of ventricular volume between groups 4 and 8 early after surgery. Patients with setting 4 had a ventricular volume reduction of 16 (standard deviation ± 9) mL while those with setting 8 had a reduction of 5 (standard deviation ± 5) mL. Constriction of subarachnoid cerebrospinal fluid spaces in cerebral high convexity and parafalcine sulci was significantly less in the setting 4 group postoperatively. There were no MRI-induced changes to valve setting after any MRI. CONCLUSIONS: Ventricular volumetry can detect shunt-induced reduction in ventricle volume early after surgery. The magnitude of reduction is related to shunt valve resistance. The Codman Certas® Plus valve is stable against MRI-induced changes in a clinical setting.
Copyright © 2025 The Author(s). Published by Elsevier Inc. All rights reserved.